Certification of Vision Impairment in Patients with Uveitis Attending a Specialist Clinic. (19th May 2019) - Jones, Nicholas P.; Pradeep, Archana; John, Binu
ABSTRACT: Purpose : To identify the causes of severe visual loss in a UK uveitis clinic, to suggest means of reducing incidence, and to propose improvement in data collection of vision impairment. Patients and methods : Retrospective case series. Results : Over 128 months, 76 (3.5–4% of patients referred) were certified as vision-impaired or severely vision-impaired. The mean age at registration was 48.4 years, 76% were of working age, and 7% were children. The diagnosis leading most often to registration was sympathetic ophthalmia and the most frequent uveitis complications were secondary cataract (whether or not operated upon) in 62%, chronic cystoid macular edema in 43%, and secondary glaucoma in 28%. Visual loss was often multifactorial. Conclusions : Severe and permanent visual loss in uveitis affects people predominantly of working age. It is probably underreported and a restructuring of the certificate of vision impairment may improve data collection. Early referral to a tertiary center may reduce the incidence of vision impairment.